Penjajahan Budaya Hallyu Pada Berbagai Sektor di Indonesia - Putri, Nada Kurnia; Latifa, Natasya Putri (LITERAKOM: Jurnal Literasi dan Komunikasi, 2023)
The advancement of information technology has caused the ease of cultures from outside to enter Indonesia. One of the cultures from abroad that enters and develops rapidly in Indonesia is Korean Culture or often referred to as Hallyu Culture. The purpose of this study is to see the influence of the development of hallyu culture in Indonesia, namely to see its influence in various sectors such as the economic, socio-cultural, and film. This study also aims to see how K-pop fans respond to the strong influence of Hallyu culture in Indonesia. The theory used in this study is Cultural Imperialism Theory, with this theory analyzed whether we are experiencing cultural colonization, because at this time hallyu culture has a strong influence in various sectors in Indonesia. This research was conducted using field observation methods and using a qualitative approach. Data collection techniques are carried out by observation or observation to one of the cafes with hallyu cultural nuances, located in Padang City. In addition to observation, we also conduct in-depth interviews, documentation, literature studies to collect data on the strong influence of hallyu culture in Indonesia in various sectors. Viewed from all aspects, it turns out that the economic, film, socio-cultural sectors have experienced the influence of hallyu culture that develops in Indonesia.